Islamic Microinsurance: Problem, Future Prospect and Sentiment Analysis - Syahdatul Maulida; Aam Slamet Rusydiana (SMART Insight, 2023)
This study aims to look at sentiments towards Islamic Micro Insurance. This research is a qualitative research with secondary data types originating from scientific publications database Dimensions. Found as many as 40 scientific publications found with related themes Islamic Micro Insurance. The data is then processed using the help software SentiStrength and the results of his research found that neutral sentiment dominated with a percentage of 58%, followed by 22% negative sentiment and 20% positive sentiment. Sentiment on scientific publication data Islamic Micro Insurance fluctuate every year. 2022 was the year with the highest number of sentiments, namely 9 sentiments, which were dominated by neutral and positive sentiments with 4 sentiments each.